2001
DOI: 10.1007/s004420000593
|View full text |Cite
|
Sign up to set email alerts
|

Changes induced by elk browsing in the aboveground biomass production and distribution of willow (Salix monticola Bebb): their relationships with plant water, carbon, and nitrogen dynamics

Abstract: Willows are dominant woody plants of many high-elevation riparian areas of the western USA, and constitute an important food resource for various ungulates, which tend to concentrate in riparian areas. The response of willow to browsing was analyzed in the elk winter range of Rocky Mountain National Park, by considering the effect of elk browsing on Salix monticola Bebb, one of the most common willow species in this area. Unbrowsed and browsed treatments were established during the 1997 growing season (May to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 33 publications
6
64
1
1
Order By: Relevance
“…3) are also of interest, both as a rough measure of plant vigor and because height gained each summer constrains annual increases in H. Analysis of treatment effects on I are complicated because we expected treatments, particularly exclosures, to affect tissue loss, and willows are known to compensate for loss by growing thicker, longer shoots (Peinetti et al 2001). We were primarily interested in the effect of treatments on I independent of those mediated by height loss; we sought to quantify treatment effects on the shape of the compensation response.…”
Section: Willow Heightmentioning
confidence: 99%
“…3) are also of interest, both as a rough measure of plant vigor and because height gained each summer constrains annual increases in H. Analysis of treatment effects on I are complicated because we expected treatments, particularly exclosures, to affect tissue loss, and willows are known to compensate for loss by growing thicker, longer shoots (Peinetti et al 2001). We were primarily interested in the effect of treatments on I independent of those mediated by height loss; we sought to quantify treatment effects on the shape of the compensation response.…”
Section: Willow Heightmentioning
confidence: 99%
“…For example, several studies on birch (genus Betula L.) and willow (genus Salix L.) showed that winter browsing led to a higher water content and higher nutrient levels of the leaves in the next growing season, probably because of an increase in the root/shoot ratio Danell et al 1994;Bryant 2003;Riipi et al 2005;Stolter et al 2005). In contrast, if the plant invests in defence (the defence response), full compensation of herbivore losses may not be achieved (Peinetti et al 2001). These plant responses to herbivore damage may in turn be important to the herbivores, affecting their growth and survival (Nykänen and Koricheva 2004) or reproduction Bryant 2003).…”
Section: Introductionmentioning
confidence: 99%
“…As plants mature and start senescing, stocks of both N and biomass are gradually re-allocated to grains, hereby invoking reduced photosynthetic capacity, discolouring of leaves and exposing of other plant pigments (Peinetti et al, 2001;Murphy and Murray, 2003;Ciganda et al, 2009). Consequently, various previous studies found that estimation of N (Zhao et al, 2014), biomass (Yang and Miller, 1985) and height (Scotford and Miller, 2004) in mature vegetation is prone to larger inaccuracies compared to in vegetation in earlier growth phases.…”
Section: Plant Traits and Plant Physiological Stagementioning
confidence: 99%